Desenvolvimento de um sistema de gerenciamento eletrônico para motores de ignição por centelha - Fabricio Jose Pacheco Pujatti (2007)
Since the conception and first built of internal combustion engine (ICE), many control intake fuel systems and spark systems are being developed. The inclusion of electronic control systems enables to optimize their efficiency, reducing the vehicle environmental impact. The task of calibration and adjustment, to this optimization, needs to electronic management systems called Electronic Computer Unit (ECU). Although exist many different manufactures, it has a high cost and an access level incompatible with the needs of an independent research group. This work are intend to design, build and test a new adjustable electronic management system, able to modify all engine work parameters, as well as the control strategies associated with this function. The development of this kind of systems is a multidisciplinary task involving experts from different areas, among other resources, high performance digital computers, as DSPs, to achieve this optimization.This work shows the methodology of the implementation, tests of a new adjustable electronic management system , their advantages and limitations. The results, which were obtained shows that developed system could get the same results of commercial systems, with the advantage of providing access conditions for the development of new control strategies, allowing, refine the research of internal combustion engines.